2010
DOI: 10.1002/da.20762
|View full text |Cite
|
Sign up to set email alerts
|

Childhood social environment, emotional reactivity to stress, and mood and anxiety disorders across the life course

Abstract: Background-Adverse child environments are associated the onset of mood and anxiety disorders in adulthood. The mechanisms underlying these life-course associations remain poorly understood. We investigate whether emotional reactivity to stress is a mechanism in the association between childhood environment characteristics and adult mood and anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 39 publications
9
142
2
5
Order By: Relevance
“…Some evidence also suggests that low calorie intake may be associated with increased physiological and emotional reactivity and cause mental problems (23,24). Therefore, to overcome hunger-related problems, it may be necessary to address social factors or stressors at home (eg, lack of control in life) with an integrated approach (11).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence also suggests that low calorie intake may be associated with increased physiological and emotional reactivity and cause mental problems (23,24). Therefore, to overcome hunger-related problems, it may be necessary to address social factors or stressors at home (eg, lack of control in life) with an integrated approach (11).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated that stress during childhood can lead later in life to greater emotional (e.g., [27]) and physiological responses to fearful or challenging events [28], leading to an imbalance in the response of the HPA axis and to an increased activity of the autonomic nervous system. Higher attachment anxiety in adulthood is positively associated with a higher cortisol response to acute stress unrelated to attachment, and correlates negatively with the cortisol response to awakening [29].…”
Section: Discussionmentioning
confidence: 99%
“…En este campo también es interesante estudiar el efecto de los factores no específi cos 5. En relación al anterior punto, se sugiere también el estudio de las variables moduladoras del efecto de las inter venciones preventivas, como género, clase social o etnia (Calvete et al, 2011;Guillham et al, 2006;Marchand , Ng, Rohde y Stice, 2010;McLaughlin et al, 2010).…”
Section: Reflexiones Y Sugerencias Para Futuros Estudiosunclassified